Desenvolvimento de imunoensaio para detecção de IgG4 específico ao alérgeno rBlo t 5 e tratamento de modelo experimental na asma aguda - Araújo, Karine Canuto Loureiro de (2019)
Allergic diseases represent a common medical condition, which has increased in recent decades, and is therefore considered a public health problem. Exposure to allergens in household dust is an important risk factor for the development of the allergic process. The Blomia tropicalis mite is known to induce respiratory allergies in tropical regions, being the Blo t 5 allergen considered of major importance. In vitro screening for IgE and IgG4 antibodies, as a diagnostic tool, is important in monitoring the immune status of patients undergoing immunotherapy to enable better prognosis in response to allergy, and to indicate specific treatments according to the immunological profile of each individual. Thus, the objectives of this work are to develop a fluorescent detection platform that facilitates the monitoring of specific allergen IgG4 antibodies, and to evaluate the effect of the combination of fluticasone fuorate and 15d-PGJ2 drugs in the treatment of acute asthma in an experimental model. To develop an IgG4 detection platform, rBlo t 5 antigens were coupled to the N-Hydroxysuccinimide (NHS) magnetic microspheres. In vitro results for IgG detection showed that the beads were functionalized with Blo t 5 allergen. A fluorescence-based magnetic beads (EFB) assay was developed, where discrimination between specimens from positive and negative patients specific to IgG4. The tool is advantageous in that it is fast and uses a small amount of sample (5µL of serum) when compared to other available tests. After diagnosis and monitoring of the allergic patient's condition, the individual is submitted to different types of treatments. For symptomatic relief of asthmatic individuals, corticosteroids are mainly used, but these medications have adverse reactions. The experimental asthma model was developed in Balb / c mice in a 14-day protocol. Animals were sensitized via i.p. on day 0, and challenged for 5 days, from day 6 to day 10 with OVA solution adsorbed in PBS solution via in, and subsequently treated under different conditions of 15-Deoxy-Delta-12,14-prostaglandin J2 (15d -PGJ2) and / or fluticasone furoate. The OVA sensitized group exhibited increased serum IgE and homogenate levels compared to the negative control group (PBS). In order to understand the best treatment for acute asthma cases and the mechanism triggered by the combination of drugs, fluticasone furoate and 15d-PGJ2, antibodies (IgE / IgG / IgG1 / IgG2a) and cytokines (IL-10 / IL-5). To consolidate the results, histological analyzes and respiratory parameter evaluation of each condition of the proposed treatments were performed. Compared to the group of mice induced by OVA, the group of animals treated with drugs alone exhibited a reduction in airway inflammation in the histological analysis. Analyzes also show that the combination of fluticasone fuorate drugs with 15d-PGJ2 is not efficient to treat an experimental model of acute asthma, since animals that received this combination of drugs showed greater pulmonary inflammatory infiltrate, higher collagen deposition in this organ and not showed improvements in respiratory function parameters. Due to the more serious adverse effects caused by glucocorticoid intervention, it is important to evaluate new forms of treatment for allergy.